The invisibility of children's paid and unpaid work : implications for Ethiopia's national poverty reduction policy - Woldehanna, T; Tefera, B; Jones, N (Sage, 2008)
The complexities of inter-generational and gendered intra-household resource allocations are frequently overlooked in poverty reduction policies. To address this lacuna, this paper focuses on links between macro-development policies and children’s paid and unpaid work burden in Ethiopia. Using a mixed methods approach, quantitative household survey data results highlight the importance of household wealth and assets, family composition and access to education services, while the qualitative results underscore the role of culturally-ascribed gendered and age-specific conceptualisations of work, parental attitudes and children’s agency. The paper concludes with a discussion of the challenges national development plans need to address to more effectively tackle childhood poverty.